Analisis Otomatisasi Kalibrator Tekanan Udara Portabel dengan Pengontrol PID dengan Metode Ziegler-Nichols dan Åström–Hägglund - Budi Santoso; Masbah R.T. Siregar; Abdul Multi; Muhammad Ridwan (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract Atmospheric pressure is one of the weather parameters that have an important role in meteorological services, especially inflight transportation. Atmospheric pressure sensors must be calibrated regularly to ensure the measurement results. The increasing number of atmospheric pressure sensors makes it impossible to calibrate in the laboratory because it can result in meteorological service downtime. Portable calibrators can be used to overcome this problem, by utilizing peristaltic pumps, solenoid valves, and microcomputers. The PID control is programmed on the microcomputer to control the speed of the peristaltik pump and the cycle of the solenoid valve to generate air pressure according to the set point determined automatically using the PID control. The Åström–Hägglund method has the lowest average stability uncertainty value at 0,003 hPa/